What does practice development (PD) offer mental health‐care contexts? A comparative case study of PD methods and outcomes. Issue 8 (3rd April 2014) - McCauley, K.; Cross, W.; Moss, C.; Walsh, K.; Schofield, C.; Handley, C.; Fitzgerald, M.; Hardy, S.
<x xml:space="preserve">Abstract</x> Accessible summary Comparing three bespoke practice development (PD) projects reveals similarities in the principles of person‐centred practice and cathartic personal growth, as relevant concepts to mental health. PD offers a collaborative approach to practice‐driven quality improvement initiatives suitable to the psychologically informed mental health context. Creating a workplace culture that allows all involved to contribute to service improvement can be achieved through embracing a PD‐driven change management strategy that aims to stimulate culturally sensitive care delivery. Abstract Practice development (PD) in mental health nursing has been progressing over the last decade; however, the level and impact of PD activity in the field of mental health remains poorly understood outside localized project impact. More specific reporting and comparative analysis of PD outcomes will improve this situation. In response, this paper presents three case scenarios from work taking place in Australia and New Zealand, as working examples of how PD methodologies have been applied within mental health practice settings. Using a comparative framework that captures the contributing assumptions, practices, processes and conditions imperative to effective PD work within a mental health‐care context, three case vignettes are reviewed. The critical question driving this paper is 'what mental health‐care services does PD offer in terms of transformational change approaches and the promotion of effective workplace cultures?' Conditions considered necessary for successful PD initiatives within mental health contexts are explored such as how PD converges and diverges with mental health‐related theories, plus where and how PD activity best integrates with the specific elements associated with mental health‐care provision. The findings are further reviewed in line with reports of PD outcomes from other fields of health care.